Pengaruh Return On Asset (Roa), Current Ratio (Cr) Dan Debt Equity Ratio (Der) terhadap Firm Value pada Perusahaan Manufaktur Otomotif di Bursa Efek Indonesia - Yuliya Fitri; Harsi Romli (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
The company's policy on financial decisions taken by the company will determine the company's performance reflecting in the results of performance ratios will ultimately increase or decrease the firm value. The manufacturing sector in financial decisions is taken by manager focused on improving the company's internal performance and measured through profitability risk ratios through the Return on Assets (ROA) ratio, liquidity risk ratio through Current Ratio (CR), and leverage ratios through the Debt Equity Ratio (DER) so that achievement of the three ratios is expected to increase investor trust to increase the company value. This research was aimed to determine the ROA, CR and DER of Firm Value (FV). The population of this research was the automotive manufacturing company listed on the IDX. The method of determining the sample used purposive sampling based on the criteria determined with 12 automotive manufacturing companies as the sample. The secondary data research data was obtained from IDX (www. Idx.co.id). The hypothesis testing used was multiple analysis techniques with the SPSS version 23 application. The data testing used was t test, that ROA had a negative effect on FV with t count -4.333 <t table 2.0141, CR had a negative effect on FV with -5.632 <2.0141 and DER had an effect on FV with 9,289> 2.0141 and ROA, CR, and DER had an effect on FV with F count 51,872> F table 4.0670. The results proved that partially ROA had a negative effect on FV, CR hada negative effect on FV, DER had a positive effect on FV. While simultaneously ROA, CR and DER had an effect on FV.